Synthesis and Characterization of Novel 1,3-Oxazepines Derived from Diamic Acid : N,N‾-Bis-(4-methyl phenyl ) pyromellitamic Diacid - Saued, Shaimaa A.; Tomma, Jumbad H.; Ali, Emad T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The symmetrical N,N‾-Bis-(4-methyl phenyl) pyromellitamic diacid (I) was synthesized from the reaction of toludine with pyromellitic dianhydride in dry acetone. Esterification of amic acid (I) with dimethyl sulphate in basic medium using acetone as a solvent give symmetrical N,N‾-bis-( 4- methyl phenyl ) pyromellitam diacetate (II). The condensation of new ester with hydrazine hydrate in ethanol leads to the formation symmetrical N,N‾-bis- (4-methyl phenyl) pyromellitamic hydrazide (III). New symmetrical 1,3-oxazepine derivatives (V)a-e can be synthesized from the reaction of the new synthesized Schiff bases (III)a-e (which are synthesized from the reaction new hydrazide (II) with different aromatic aldehyde) with naphthalic anhydride in dry benzene . The synthesized compounds have been characterized by their melting points and by their spectral data, FTIR and 1HNMR spectroscopy of compound (V)c.